Kościół, religia i religijność a polskie życie polityczne w Galicji doby autonomii. Stan badań i postulaty badawcze - Szymczak, Damian (Wydawnictwo Uniwersytetu Rzeszowskiego, 2023)
Rola Kościoła katolickiego w dziejach państwa i społeczeństwa polskiego jest ogromna. Dodatkowego znaczenia Kościół nabrał w okresie narodowej niewoli. Księża niejednokrotnie angażowali się w działalność patriotyczną, świeccy szukali oparcia w religii. Wraz z rozwojem nacjonalizmu dochodziło do coraz większej symbiozy narodu z katolicyzmem. Angażowanie się księży w działania polityczne przynosiło również napięcia polityczne, szczególnie w autonomicznej Galicji. Dotychczas brak jest syntezy poświęconej analizie miejsca duchowieństwa katolickiego i religii w galicyjskiej kulturze politycznej. Niniejszy artykuł jest próbą przybliżenia dotychczasowego dorobku naukowego w tej materii oraz postawienia kilku postulatów badawczych.

The role of the Catholic Church in the history of the Polish state and society is immense. The Church gained additional significance during the period of national subjugation. The clergy often engaged in patriotic activities, while the laity sought solace in religion. With the development of nationalism, there was an increasing symbiosis between the nation and Catholicism. The involvement of priests in political actions also caused political tensions, particularly in the autonomous Galicia. So far, there has been a lack of synthesis dedicated to analysing the place of the Catholic clergy and religion in Galician political culture. This article attempts to present a summary of the scholarly achievements in this field and put forward several research postulates.
Church, religion and religiosity with regard to Polish political life in Galicia in the era of autonomy. State of the research and research postulates
Keywords: Galicja; Kościół katolicki; kultura polityczna; religijność; autonomia; Galicia; Catholic Church; political culture; religiosity